2020
DOI: 10.1037/amp0000652
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging human-centered design to implement modern psychological science: Return on an early investment.

Abstract: Although classic models of implementation emphasized the importance of innovation characteristics in their adoption and sustained use, contemporary implementation research and practice have deprioritized these variables. Human-centered design (HCD) is an approach that grounds product development in information collected about the people and settings that will ultimately use those products. HCD has strong roots in psychological theory, but its application is typically limited to the development of digital techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 78 publications
(127 reference statements)
0
67
0
2
Order By: Relevance
“…It is also novel in its consideration of user-centered design principles (eg, ease of use and learnability) when developing and identifying DMHT features that would be most acceptable to a very large sample of potential target consumers. Consistent with emerging models that integrate community-based research, implementation science, and user-centered design principles [ 57 , 58 ], this is an important first step in a well-planned process of DMHT design to identify the needs and preferred features that users, both experienced and unexperienced, and preferences for what tools they would like to see in a DMHT. Previous studies that used self-report of physical health and mental health apps found that users typically only use an app for one feature [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also novel in its consideration of user-centered design principles (eg, ease of use and learnability) when developing and identifying DMHT features that would be most acceptable to a very large sample of potential target consumers. Consistent with emerging models that integrate community-based research, implementation science, and user-centered design principles [ 57 , 58 ], this is an important first step in a well-planned process of DMHT design to identify the needs and preferred features that users, both experienced and unexperienced, and preferences for what tools they would like to see in a DMHT. Previous studies that used self-report of physical health and mental health apps found that users typically only use an app for one feature [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these recommendations can be easily incorporated into the design of future DMH tools; however, the challenge of successful DMH implementation is still significant. Achieving successful and sustainable integration of digital tools into a predigital health system will likely require collaboration between specialists in DMH and implementation [33][34][35][36][37] and a shift from randomized controlled trials to effectiveness-implementation hybrid trials [38]. Only then can the field build evidence on how DMH tools can be successfully embedded into the daily work of clinical settings and have continued success without research support.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Lyon ,dkk melakukan peninjauan terhadap HCD dimana HCD bukanlah metode itu sendiri, tetapi bidang yang menggunakan pendekatan kuantitatif, kualitatif, dan metode campuran untuk menyelaraskan produk dengan konteks penggunaan. Pengumpulan informasi untuk HCD sering kali secara inheren merupakan metode campuran, sangat bergantung pada penyelidikan kualitatif untuk memahami batasan kontekstual dan kebutuhan pengguna, serta data kuantitatif untuk membandingkan desain alternatif atau mengevaluasi produk melalui beberapa iterasi [4].…”
Section: Tinjauan Pustakaunclassified